(3cJGH aj Yde GdJTQjMs
(3ChdgG (B:s
(3Yde GdJTQjM Yde jHMK ajg Yf CYVGA GdEfSGf hcjajI JQcjHgG ef SHYI CYXe LOQGf CMOgeG Ybe GdLHgI JeJW ef WQa GdbMa Edi BNQ GdMGLH s
(3BNQgG (B:s
(3hdjS jUjH GdeDef hUH hdGfUH MJi jTGcgG EdG caQ HgG ef NWGjGg ChQaY HgG OQLGJ, ceG UM ai GdMOjK s
(3Vef eLehY , JQJjHgG (B: (3ef U (B52 - (3U(B560s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B204 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs